AN ANALYSIS OF SUNDANESSE TEXTBOOK IN UNPAD.AC.ID: A CRITICAL DISCOURSE ANALYSIS - Humaira Restu Maulidia; Cita Mustika Kusumah; Dien Novita (Universitas Widyatama, 2023)
The current study investigates the representation of UNPAD, which raises the issue of Sundanese textbooks on the UNPAD website. It focuses on how the article entitled